Pengaruh Kualitas Pelayanan Kesehatan dan Sarana Prasarana Terhadap Loyalitas Pasien Melalui Kepuasan Pasien - indah pertiwi (An Idea Nursing Journal, 2022)
The growing competition between hospitals is getting tougher so that every hospital is required to enhance competitiveness by trying to give satisfaction to all its patients. The progress and development of the hospital will depend on the quality of the services provided. Hospital growth in Indonesia is quite high in the past ten years. However, this growth does not indicate good quality. Data from the Hospital Accreditation Commission in 2014 recorded that only 535 hospitals were nationally accredited from 2424 hospitals registered in Indonesia or around 22 percent. This study was conducted with the aim of analyzing the effect of the quality of health services and infrastructure on patient loyalty through patient satisfaction at the Jala Ammari Hospital in Makassar. This research used quantitative research by using path analysis method. The population in this study was 1,432 patients. The number of samples was 115 patients. The sampling technique in this study is random sampling. The results of this study indicate that the significance value of (1) the effect of health service quality on patient loyalty is 0.016, (2) infrastructure facilities on patient loyalty is 0.017 (3) the quality of health services to patient satisfaction is 0.000, (4) infrastructure facilities to patient satisfaction of 0.043, (5) patient satisfaction on patient loyalty is 0.025, (6) the effect of health service quality on patient loyalty through patient satisfaction is 0.044, (7) the effect of infrastructure on patient loyalty through patient satisfaction is 0.258. The conclusion that the quality of health services goes well so as to increase patient loyalty through patient satisfaction, but seen from the facilities has not been implemented properly on patient loyalty through patient satisfaction.